PENGAMBILAN GAMBAR KOMPOSISI SEPERTIGA BIDANG DALAM FILM DAMAR KURUNG MASMUNDARI - Rahmansyah, Muhamad Aulia; Triadiputra, St.Andre (Seni Media Rekam ISI Surakarta, 2016)
The idea of this research, Damar Kurung Masmundari, is how Masmundari's struggle to preserve arts tradition in Gresik by using third composition visual field expository documentary. Duration of this documentary movie is 26 minutes and showing a reconstruction of Masmundari as an artist Damar Kurung. The benefit is to show the proportion and composition of subject and object trough the rule of thirds.In addition, this research shows the point of interest of Damar Kurung proportion to attract the audience. The rule of thirds technique is used because subject in Damar Kurung Masmundari movie showed focused as well as symmetries being a point of interest.Keywords : documentary,expository,Damar Kurung Masmundari,and exploration.